Interest Rates, Sanitation Infrastructure, and Mortality Decline in Nineteenth-Century England and Wales. (18th March 2022) - Chapman, Jonathan
Abstract : This paper investigates whether high borrowing costs deterred investment in sanitation infrastructure in late nineteenth-century Britain. Town Councils had to borrow to fund investment, with considerable variation in interest rates across towns and over time. Panel regressions, using annual data from more than 800 town councils, indicate that higher interest rates were associated with lower levels of infrastructure investment between 1887 and 1903. Instrumental variable regressions show that falling interest rates after 1887 stimulated investment and led to lower infant mortality. These findings suggest that Parliament could have expedited mortality decline by subsidizing loans or facilitating private borrowing.